2006
DOI: 10.1207/s15327663jcp1604_9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corporate Social Responsibility (CSR) Activities on Companies With Bad Reputations

Abstract: Based on theories of attribution and suspicion, three experiments highlight the mediating role of perceived sincerity of motives in determining the effectiveness of CSR activities. CSR activities improve a company's image when consumers attribute sincere motives, are ineffective when sincerity of motives is ambiguous, and hurt the company's image when motives are perceived as insincere. Variables affecting perceived sincerity include the benefit salience of the cause, the source through which consumers learn a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
883
9
19

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,068 publications
(954 citation statements)
references
References 42 publications
43
883
9
19
Order By: Relevance
“…Consequently, consumers may evaluate companies more negatively when the CSR information is provided by the company itself and more positively when an external source informs them about CSR efforts (Kim 2011;Yoon et al 2006). This may result from perceived self-interest in the eyes of consumers (i.e., self-promoter's paradox; Ashforth and Gibbs 1990): Information from the company is perceived as being selfinterested, calling into question the credibility of the message and the company itself, whereas external information creates less bias and is perceived as more credible.…”
Section: The Self-promoters Paradox and Greenwashingmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, consumers may evaluate companies more negatively when the CSR information is provided by the company itself and more positively when an external source informs them about CSR efforts (Kim 2011;Yoon et al 2006). This may result from perceived self-interest in the eyes of consumers (i.e., self-promoter's paradox; Ashforth and Gibbs 1990): Information from the company is perceived as being selfinterested, calling into question the credibility of the message and the company itself, whereas external information creates less bias and is perceived as more credible.…”
Section: The Self-promoters Paradox and Greenwashingmentioning
confidence: 99%
“…Whereas internal CSR communication itself will thus rather be perceived as extrinsic, positive external CSR communication should drive attributions to intrinsic motives due to higher levels of credibility and trust (Parguel et al 2011;Becker-Olsen et al 2006). Prior research found that consumers are more likely to have negative attitudes, beliefs, and behaviors toward the organization when they assign extrinsic motives compared to intrinsic motives (Becker-Olsen et al 2006;Ellen et al 2006;Mohr et al 1998;Yoon et al 2006).…”
Section: The Mediating Role Of Motives: Attribution Theorymentioning
confidence: 99%
“…Higher levels of advertising increase customers' brand awareness and may stimulate customers to become further informed about the brand, including its CSR policies. Advertising specifically related to CSR may improve consumer awareness of a brand's CSR, thus enhancing the impact of CSR, although advertising featuring CSR may also backfire (Servaes and Tamayo 2013;Yoon et al 2006).…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…Kim et al (2010) empirically studied both CV and CSR perceptions; however, the relationship between these particular variables was not tested nor was the impact on consumers investigated. Furthermore, research has shown considerable benefits of the communication of various CSR initiatives (Sen and Bhattacharya, 2001;Yoon, Gurhan-Canli and Schwarz, 2006) but little is known about the impact of CV and the process by which it could influence the CSR image and overall image of the firm.…”
Section: Corporate Social Responsibility Imagementioning
confidence: 99%